Quality of life of children with attention-deficit/hyper activity disorder - Pongwilairat K. (2014)
Objective: Attention-deficit/hyperactivity disorder (ADHD) has an impact on children and families. The purpose of this study was to assess the health-related quality of life between school-age children with ADHD compared with those without physical or mental disorders. Material and Method: Self- and parent-reports describing the quality of life, covering 4 domains: physical, emotional, social, and school functioning, were obtained from 46 children with ADHD and 94 control children. At the time of the study, 17 of 46 children reported receiving medication for ADHD. Results: After controlling for age and demographic background, both children with ADHD and their parents reported having a significantly lower quality of life score than controls and their parents. Children with ADHD also reported themselves to have a significantly low physical score, despite their physically healthy status. Conclusion: Children with ADHD had impairment of their quality of life in the physical and psychosocial domains. Improvement of health-related quality of life should be integrated in the overall planning of the treatment goals.